Submarine venting of magmatic volatiles in the Eastern Manus Basin, Papua New Guinea. (15th August 2015) - Seewald, Jeffrey S.; Reeves, Eoghan P.; Bach, Wolfgang; Saccocia, Peter J.; Craddock, Paul R.; Shanks, Wayne C.; Sylva, Sean P.; Pichler, Thomas; Rosner, Martin; Walsh, Emily
Abstract: The SuSu Knolls and DESMOS hydrothermal fields are located in the back-arc extensional transform zone of the Eastern Manus Basin. In 2006, highly acidic and ΣSO4 -rich vent fluids were collected at both sites and analyzed for the chemical and isotopic composition of major and trace species. Fluids exiting the seafloor have measured temperatures from 48 to 215 °C and are milky white in appearance due to precipitation of elemental S 0 . Vent fluid concentrations of Na, K, and Mg are depleted by as much as 30% relative to seawater, but have the same relative abundance. In contrast, the fluids are highly enriched in dissolved ΣCO2, Cl, SiO2(aq), Fe, and Al relative to seawater. Measured pH (25 °C) ranged from 0.95 to 1.87 and aqueous ΣSO4 ranged from 35 to 135 mmol/kg. The chemical and isotopic composition points to formation via subsurface mixing of seawater with a Na-, K-, Mg-, and Ca-free, volatile-rich magmatic fluid exsolved from subsurface magma bodies during a process analogous to subaerial fumarole discharge. Estimates of the magmatic end-member composition indicate a fluid phase where H2 O > SO2 > CO2 ≈ Cl > F. The hydrogen and oxygen isotopic composition of H2 O and carbon isotopic composition of ΣCO2 in the vent fluids strongly suggest a contribution of slab-derived H2 O and CO2 to melts generated in the mantle beneath the Eastern Manus volcanic zone. Abundant magmatically-derived SO2 undergoes disproportionation during cooling in upflow zones and contributes abundant acidity, SO4 2−, and S 0 to the venting fluids. Interaction of these highly acidic fluids with highly altered mineral assemblages in the upflow zone are responsible for extensive aqueous mobilization of SiO2(aq), Fe, and Al. Temporal variability in the speciation and abundance of aqueous S species between 1995 and 2006 at the DESMOS vent field suggests an increase in the relative abundance of SO2 in the magmatic end-member that has mixed with seawater in the subsurface. Results of this study constrain processes responsible for the formation of hot-spring fluids in magmatically active back-arc environments and the resulting chemical exchange between the lithosphere and water column.